Evaluación de cuatro dietas comerciales® en la pigmentación de piel y rendimiento productivo de pollos COBB-500 - Pin Napa, Rubén Patricio (2024)
This research evaluated the effects of four commercial® diets on the productive performance and skin pigmentation of Cobb 500 chickens over a 6-week period. A completely randomized experimental design was applied with 20 experimental units, 4 treatments, and 5 replicates, assigning a commercial diet to each treatment (diet 1, diet 2, diet 3, diet 4). Weekly measurements were taken for weight gain, feed conversion, and feed intake, and at the end of the growing period, weight, carcass yield, skin pigmentation, feet, and beak were evaluated. The results show that diet 4 achieved the highest weekly and final weight gain; however, it had the highest accumulated feed intake and conversion. On the other hand, diet 2 performed well during the growing period, averaging 2566.28 ± 220.34 g and standing out with the lowest feed conversion ratio of 1.9 g/g compared to the other diets, making it the most profitable. No significant differences were found in carcass yield or skin pigmentation between treatments. In conclusion, commercial diet 2 offers good productive indices, with lower feed intake and conversion, and a better cost-benefit ratio, making it recommended for broiler chicken production due to its productive efficiency and cost-benefit relationship.